Pengembangan Informasi Pelayanan melalui Perancangan Aplikasi SobatTirta dalam Meningkatkan Kepuasan Pelanggan PERUMDA Tirta Anai - Dewi, Alifa Permata; Alva Dian Fadhila (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
PERUMDA Tirta Anai is a regional company engaged in the distribution of water supplied throughout Padang Pariaman Regency. This company already has an information system through social media, by sharing informational posts with customers, as well as a complaint hotline which function as channels for customers to report issues. However, this system still has shortcomings, namely a lack of quick response in addressing customer problems, as well as limitations in conveying detailed information, which tends to be fragmented across social media, the complaint hotlineg. To address these issues, the SobatTirta Application was designed to facilitate access to the services provided by PERUMDA Tirta Anai through various features. The method used is descriptive qualitative with the design of the SobatTirta Application prototype. The results show that the application design can be beneficial for both customers and PERUMDA Tirta Anai. Therefore, the design of the SobatTirta Application is expected to enhance service satisfaction and provide further information for Tirta Anai customers.